Pathogenomics Characterization of an Emerging Fungal Pathogen, Fusarium oxysporum f. sp. lycopersici in Greenhouse Tomato Production Systems - Adhikari, Tika B.; Gao, Anne; Ingram, Thomas; Louws, Frank J. (Frontiers in Microbiology, 2020)
In recent years, greenhouse-grown tomato (Solanum lycopersicum) plants showing vascular wilt and yellowing symptoms have been observed between 2015 and 2018 in North Carolina (NC) and considered as an emerging threat to profitability. In total, 38 putative isolates were collected from symptomatic tomatoes in 12 grower greenhouses and characterized to infer pathogenic and genomic diversity, and mating-type (MAT) idiomorphs distribution. Morphology and polymerase chain reaction (PCR) markers confirmed that all isolates were Fusarium oxysporum f. sp. lycopersici (FOL) and most of them were race 3. Virulence analysis on four different tomato cultivars revealed that virulence among isolates, resistance in tomato cultivars, and the interaction between the isolates and cultivars differed significantly (P < 0.001). Cultivar ‘Happy Root’ (I-1, I-2, and I-3 genes for resistance) was highly resistant to FOL isolates tested. We sequenced and examined for the presence of 15 previously described putative pathogenicity genes from different classes (Fmk1, Fow1, Ftf1, Orx1, Pda1, PelA, PelD, Pep1, Pep2, eIF-3, Rho1, Scd1, Snf1, Ste12, and Sge1), and 14 Secreted In Xylem (SIX) effector genes to use as genetic markers to identify and differentiate pathogenic isolates of FOL. Sequence data analysis showed that five pathogenicity genes, Fmk1, PelA, Rho1, Sge1, and Ste12 were present in all isolates while Fow1, Ftf1, Orx1, Peda1, Pep1, eIF-3, Scd1, and Snf1 gene products were dispersed among isolates. Two genes, Pep2 and PelD, were absent in all isolates. Of the 14 SIX effectors assessed, eight genes (SIX1, SIX3, SIX5, SIX6, SIX7, SIX8, SIX12, and SIX14) were identified in most isolates while the remaining SIX genes varied among isolates. All isolates harbored one of the two mating-type (MAT-1 or MAT-2) idiomorphs, but not both. The SIX4 homolog was present only in race 1 isolates. Diversity assessments based on sequences of the SIX3 the effector- and translation elongation factor-1α encoding genes SIX3 and tef1-α, respectively were the most informative to differentiate pathogenic races of FOL and resulted in race 1, forming a monophyletic clade while race 3 comprised multiple clades.